1994
DOI: 10.1093/carcin/15.12.2905
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogen—DNA adducts and gene mutation in foundry workers with low-level exposure to polycyclic aromatic hydrocarbons

Abstract: Carcinogen-DNA adducts and somatic gene mutation at the hypoxanthine guanine phosphoribosyl transferase (HPRT) locus were evaluated in peripheral leukocytes of workers in an iron foundry with exposure to benzo[a]pyrene (B[a]P) and other polycyclic aromatic hydrocarbons (PAHs). During the two year study period, B[a]P exposure declined by approximately 40%, from a maximum of 60 ng/m3 in the first year to < 36 ng/m3 1 year later. A total of 64 persons were sampled in November/December of the two successive study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…There is sufficient circumstantial evidence to assume that DNA adducts are actually related to cancer risk in man. For example, Perera et al (1994) reported a correlation between DNA adduct levels and the in vivo mutation frequency in individuals occupationally exposed to PAH. Although the gene (HPRT) and tissue (white blood cells, WBC) under investigation, are not relevant in occupationally related carcinogenesis, their results provide evidence for the mutational effects of PAH in vivo in humans.…”
Section: Studies In Humansmentioning
confidence: 99%
“…There is sufficient circumstantial evidence to assume that DNA adducts are actually related to cancer risk in man. For example, Perera et al (1994) reported a correlation between DNA adduct levels and the in vivo mutation frequency in individuals occupationally exposed to PAH. Although the gene (HPRT) and tissue (white blood cells, WBC) under investigation, are not relevant in occupationally related carcinogenesis, their results provide evidence for the mutational effects of PAH in vivo in humans.…”
Section: Studies In Humansmentioning
confidence: 99%
“…Similarly, reference number [21] reported a link between carcinogen DNA adducts and somatic gene mutation at the hypoxanthine guanine phosphoribosyl transferase locus in an iron foundry workers exposure to benzo[a]pyrene and other polycyclic aromatic hydrocarbons (PAHs).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have examined whether baseline levels of micronutrients (vitamins C, E, ,-carotene, or retinol) in the serum of persons who have not been treated with chemoprevention are inversely related to genetic damage (9,13). In a cross-sectional study of 63 heavy smokers, the serum concentrations of a-tocopherol (cholesterol-adjusted), ascorbic acid, 1-carotene, and retinol were evaluated in relationship to the levels of PAH-DNA adducts in lymphocytes measured in the same individuals (14).…”
Section: Chemopreventionmentioning
confidence: 99%